2011
DOI: 10.2337/dc10-1233
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Replacement in Hypogonadal Men With Type 2 Diabetes and/or Metabolic Syndrome (the TIMES2 Study)

Abstract: OBJECTIVEThis study evaluated the effects of testosterone replacement therapy (TRT) on insulin resistance, cardiovascular risk factors, and symptoms in hypogonadal men with type 2 diabetes and/or metabolic syndrome (MetS).RESEARCH DESIGN AND METHODSThe efficacy, safety, and tolerability of a novel transdermal 2% testosterone gel was evaluated over 12 months in 220 hypogonadal men with type 2 diabetes and/or MetS in a multicenter, prospective, randomized, double-blind, placebo-controlled study. The primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
448
1
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 485 publications
(484 citation statements)
references
References 25 publications
21
448
1
14
Order By: Relevance
“…26 Any benefit on glucose metabolism or visceral adiposity in obese men with type 2 diabetes could not be demonstrated in another recent trial. 27 Wang et al summarised the results of several trials that evaluated the metabolic effect of testosterone replacement.…”
Section: Discussionmentioning
confidence: 99%
“…26 Any benefit on glucose metabolism or visceral adiposity in obese men with type 2 diabetes could not be demonstrated in another recent trial. 27 Wang et al summarised the results of several trials that evaluated the metabolic effect of testosterone replacement.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64][65] In the TIMES2 (Testosterone Replacement In Hypogonadal Men With Either Metabolic Syndrome or Type 2 Diabetes) study, 6 to 12 months of transdermal TRT (vs placebo) significantly improved insulin resistance and glycemic control in a large randomized study of hypogonadal men with type 2 diabetes mellitus (ACCF/AHA class Ib). 66 A meta-analysis of 5 other randomized controlled trials (including 3 placebo-controlled trials) with mean follow-up of 58 weeks found that TRT was associated with a significant reduction in fasting plasma glucose levels, homeostasis model assessment of insulin resistance index, triglycerides, and WC. An increase in HDL cholesterol level was also observed, whereas no significant differences were observed for total cholesterol level, BP, or BMI.…”
Section: Recommended Assessments and Risk Clarificationmentioning
confidence: 99%
“…The effects of testosterone treatment on lipids in double-blind placebo-controlled RCTs are shown in Table 2. In the TIMES2 study Jones et al (2011) found not only a significant decrease in lipoprotein a (Lpa), an independent risk factor for cardiovascular disease, but also a significant decrease in the theoretically protective HDL cholesterol. Patients with metabolic syndrome additionally had reduced total and LDL cholesterol after 6 months of testosterone therapy compared with placebo (Table 2).…”
Section: Testosterone Lipids and Blood Pressurementioning
confidence: 99%
“…Six RCTs have been conducted to date specifically in men with diabetes or the metabolic syndrome (Kapoor et al 2006, Gopal et al 2010, Kalinchenko et al 2010, Jones et al 2011; Tables 1 and 2). One was never unpublished (http://www.solvaypharmaceuticals.com/ static/wma/pdf/1/3/4/4/2/S176.2.101.pdf) and one has been presented in preliminary abstract form (Hackett et al 2013).…”
Section: Testosterone Treatment In Men With Metabolic Disordersmentioning
confidence: 99%